The Multidimensional Usefulness of Grounded Theories Editorial - Astrid Gynnild (Grounded Theory Review: An International Journal)
This issue of the Grounded Theory Review demonstrates the multidimensional usefulness of doing grounded theories. Raising awareness through systematized conceptualizing is undoubtedly the number one reason for generating grounded theories. But, as demonstrated in the conceptual discussion of applying GT by Barney G. Glaser, raising awareness is just one of many benefits of the method.